Translating Renaissance experience - Müller-Wood, Anja, 1969-; Adamczewski, Tymon; Gill, Patrick (Literary critic) (Vita traductiva ;, 2021)
A period of intense intercultural activity, the Renaissance offers a productive terrain for exploring the multi-faceted dimensions of translation. Translation Studies increasingly sees translation as a process of cultural interaction in which multiple agents participate. The essays in this volume show how experience, diversely conceptualised, profoundly shapes this interaction at both the level of production and reception. By examining how Renaissance experience was translated at the time into textual and material forms (Milton, Sidney, Donne) and how Renaissance textual sources (Middleton, Piccolomini, Shakespeare) or the idea of the Renaissance have been experienced retrospectively through theatre adaptations, philosophical readings, video games, or theories of multimodality, these essays illuminate the rich complexity of translation and reaffirm the continuing relevance of the Renaissance.